Revision of the Neotropical genus Protoconnus Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
The Neotropical genus Protoconnus Franz, belonging to the tribe Glandulariini, is revised. Protoconnus is redefined based on detailed morphological study, and all known species are revised, including 10 originally placed in Protoconnus, one transferred from Euconnus, and 14 described as new. The following species are treated: P. andicola Franz (Peru), P. peruensis Franz (Peru), P. minutus Franz (Peru), P. minutissimus Franz (Peru), P. venezolanus Franz (Venezuela), P. araguanus Franz (Venezuela), P. bolivianus Franz (Bolivia), P. comarapae Franz (Bolivia), P. robustus Franz (Bolivia), P. paraguayanus Franz (Paraguay), P. princeps (Franz), comb. n. (ex Euconnus) (Peru), P. quillabambanus sp. n. (Peru), P. ecuadoranus sp. n. (Ecuador), P. napoanus sp. n. (Ecuador), P. magnus sp. n. (Ecuador), P. impressifrons sp. n. (Bolivia), P. angustus sp. n. (Bolivia), P. acutus sp. n. (Bolivia), P. tunarianus sp. n. (Bolivia), P. apaapa sp. n. (Bolivia), P. maximus sp. n. (Costa Rica), P. minusculus sp. n. (Costa Rica), P. costaricanus sp. n. (Costa Rica), P. inexpectatus sp. n. (Costa Rica), and P. volcanbaru sp. n. (Panama). Lectotypes are designated for P. andicola and P. peruensis.